Uji Kinerja Pengolahan Traktor Roda Empat Model At 5470 Dengan Bajak Piring (Disk Plow) Pada Tanah Dilahan Percobaan BPTP Sumatera Barat - Leni, Desmarita; Selviyanty, Veny; Perdana Kusuma, Yuda (SURYA TEKNIKA, 2022)
The use of tractors as a source of propulsion in land cultivation for agriculture is expected to ease the work of farmers and speed up the processing time of the land. This study tested the performance of the Iseki AT 5470 4-wheel tractor using a disk plow on dry soil in the pilot land of the West Sumatra AIAT. The 4-wheel tractor test was carried out on land with a size of 20 X 10 meters. The plowing pattern used in the study was a plow pattern from the edge. The measurement of the width of the plow using the plow implement was 1 meter and the depth of the plow was 15.7 cm. The efficiency of the tractor was 69.63% with fuel consumption of 6.5 liters. The low efficiency of the tractor is due to the processing area being too small, so there are many turns that waste a lot of time during testing